New epigraphical sourses about plague epidemic 1654 in the Moscow Russia - Avdeev Aleksandr (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
In the article are published two epigraphical monuments from Galich (the modern regional center of Kostroma region) — a bouldery gravestone of the middle of 50 th of XVII century from a necropolis of Bogojavlenskaja churches and the inscription of 1778/79 which have been rapped out on a salary of an icon of the Saviour Not Made by Hands, of cathedral Vvedensky church being in an iconostasis. Both epigraphical monuments are connected with plague epidemic was spread in Russian state in 1654— 1655. In article also questiones the chronology and borders of epidemic spreading.